2021
DOI: 10.1111/coa.13844
|View full text |Cite
|
Sign up to set email alerts
|

Virus load and incidence of olfactory, gustatory, respiratory, gastrointestinal disorders in COVID‐19 patients: A retrospective cohort study

Abstract: Objectives: This study investigated the relationship between viral load and the incidence of olfactory and gustatory dysfunction (OD and GD), the incidence of respiratory and gastrointestinal symptoms and the recovery of OD and GD in COVID-19 patients.Design: A retrospective cohort study. Setting and Participants:This study was conducted on 599 outpatients' cases in Golestan province between February and June 2020. Main Outcome Measures:The incidence, severity (complete or partial) and recovery time of OD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…We revealed that patients who had olfactory/gustatory impairment had a considerably shorter time until viral clearance. Taziki Balajelini et al observed greater CT values and lower viral load in individuals with olfactory or gustatory impairment, which is consistent with our findings [ 59 ]. In opposition to our observation, several studies reported lower CT values and a long time until viral clearance and the recovery of olfactory/gustatory disorders [ 13 , 60 ], while Cho et al found no association between the CT value and olfactory/gustatory impairment degree or recovery duration [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…We revealed that patients who had olfactory/gustatory impairment had a considerably shorter time until viral clearance. Taziki Balajelini et al observed greater CT values and lower viral load in individuals with olfactory or gustatory impairment, which is consistent with our findings [ 59 ]. In opposition to our observation, several studies reported lower CT values and a long time until viral clearance and the recovery of olfactory/gustatory disorders [ 13 , 60 ], while Cho et al found no association between the CT value and olfactory/gustatory impairment degree or recovery duration [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…We read with interest the retrospective cohort study reported by Taziki Balajelini et al, 1 The findings of the study may be counterintuitive to many since increased viral load would be expected to lead to more widespread damage to the olfactory and gustatory epithelium. Nevertheless, the observations coincide with the findings of a meta-analysis 2 in which severely ill patients with COVID-19 had a lower odd of experiencing OD than non-severely ill patients with COVID-19 (odds ratio=0.527; 95% confidence interval 0.373-0.744); the viral loads have been associated directly with disease severity in patients with COVID-19, and therefore, patients with OD and/or GD who had a low viral load (as reported in the study 1 ) would be expected to experience milder illness.…”
Section: Physiological Plausibility Of Lower Viral Load In Patients W...mentioning
confidence: 96%
“…We read with interest the retrospective cohort study reported by Taziki Balajelini et al, 1 which investigated the relationship between viral load and the incidences of olfactory dysfunction (OD) and gustatory dysfunction (GD) in patients with COVID‐19. In the study, the authors observed a significantly higher ( p =0.001) mean cycle threshold (Ct) value of RT‐PCR test for SARS‐CoV‐2 among patients with (28.13±4.55) OD compared to their counterparts without OD (26.91±4.49).…”
mentioning
confidence: 99%
“…In total candidate vaccines, 194 and 123 are in clinical and preclinical phases, respectively, that are available at https://www.who.int/publications/m/item/draft-landscape-of-covid-19-candidate-vaccines . There are 10 platforms for COVID-19 vaccines including, PS, nonreplicating viral vector (VVnr), replicating viral vector (VVr), VVnr in combination with an antigen-presenting cell (VVnr + APC), VVr in combination with an antigen-presenting cell (VVr + APC), virus-like particle, inactivated virus, live attenuated virus, mRNA vaccine (RNA), and DNA [ 30 , 81 , 82 ]. Around 11 vaccine candidates have been authorized/approved up to now in clinics and markets worldwide.…”
Section: Vaccinesmentioning
confidence: 99%